Legal Protection Of A Child’s Citizenship Status In Mixed-Nationality Marriages In Indonesia - Nurlina; Ahmad Zuhry Amir; Imran; Firman Batari; Abdul Salam (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
Mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA) have increasingly raised complex legal issues, particularly regarding the citizenship status of children born from such unions. This study aims to analyze the legal protection of children’s citizenship status under Indonesian law and to examine the legal aspects of children’s status in mixed marriages. This research employs a normative juridical method using secondary legal materials, including primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The findings indicate that Law No. 12 of 2006 on Citizenship grants children of mixed marriages a limited dual citizenship status until the age of 18 or at most 21 years, after which they must choose one nationality. However, implementation remains problematic due to inadequate socialization, risk of statelessness, and restricted civil rights — including inheritance of land — for dual-citizen children under the Basic Agrarian Law. Weak inter-agency coordination among the Directorate General of Immigration, Civil Registry, and the Ministry of Law further compounds these challenges. This study concludes that harmonization of citizenship law with other related regulations, along with an integrated administrative system, is urgently needed to ensure substantive legal protection for children of mixed marriages.